Strategic Issues at Energy Efficiency Policy of Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article shows the main trends in world energy markets, which determine energy policy, summarizes the scope and strategic objectives. A comparative analysis of energy efficiency, availability of energy resource in region and individual countries was conducted. The structure and dynamics of the formation of energy sources in Ukraine, the structure of their use, import dependence were evaluated. Major activities that are included into the strategy energy efficiency were estimated. Pointed their strengths and weaknesses. The basic ways of improvement of the strategic objectives in terms of complex energy policy formation. It should be part of country Socio-economic Development Strategy and determine the basic guidelines for regional programs of energy efficiency, including national and regional energy efficiency indicators, effective mechanisms of its stimulation and adapt to the economic and political situation in the country.